(untitled) (Journal of Pathology of Nepal, 2022)
Background: Prostate-specific antigen density has been suggested to enhance the diagnostic efficacy of serum prostate-specific antigen alone in detecting prostate cancer, thereby reducing unnecessary biopsies and associated morbidities. This study aimed to assess the diagnostic performance of prostate-specific antigen density in detecting prostate cancer. Materials and methods: A retrospective analysis of histologically proven benign and malignant prostate diseases, submitted in the histopathology department was performed from April 2019 to March 2020. The diagnostic performance of prostate-specific antigen density was assessed and its optimum cut-off value was determined using the receiver operating characteristic curves. The diagnostic efficacy of prostate-specific antigen density was also compared with prostate-specific antigen in detecting prostate cancer. Results: The AUC to predict prostate cancer was 0.89 (95% CI 0.79-0.98. p <0.001) for prostate-specific antigen density. The diagnostic performance of prostate-specific antigen density at cut-off 0.18 ng/ml/cc was better than prostate-specific antigen alone (AUC, 0.838 vs 0.662). Sensitivity was 80% for both prostate-specific antigen density at cut-off 0.18 ng/ml/cc and prostate-specific antigen. But, prostate-specific antigen density had a higher specificity of 87.7 % than prostate-specific antigen (52.3%)and thus it could better distinguish benign diseases from prostate cancer. It would have reduced unnecessary biopsy by 35%. Conclusions: The diagnostic efficacy of prostate-specific antigen density was good and it was found to be a better predictor of prostate cancer at the cut-off value of 0.18ng/ml/cc when compared to prostate-specific antigen alone.